Tumorigenic effect mediated by fatty acid synthase in a murine mammary adenocarcinoma model fed with high palmitic acid and fructose diet - Mazo, Tamara Magali (2022)
Fil: Mazo, Tamara Magali. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico; Argentina.